using remainder theorem find the remainder on dividing 3x2 + 5x - 11 by 2x + 5
Answers
Answered by
11
Answer:
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/de1/2bae17439c6f21d2fe3b239395e8a832.jpg)
![](https://hi-static.z-dn.net/files/d9e/f3d93befc0d48e42221e05d7eefed011.jpg)
Answered by
1
Answer:
The remainder obtained on dividing 3x² + 5x - 11 by 2x + 5 =
Step-by-step explanation:
Recall the theorem
When a polynomial f(x) is divided by a linear polynomial x-a, the remainder will be equal to f(a)
Given,
f(x) = 3x²+5x-11
2x +5 = 0 ⇒ x =( ) ⇒ x-(
) = 0
The by remainder theorem,
The remainder obtained when f(x) is divided by x-( ) is f(
)
f( ) = 3(
)²+5(
)-11
= 3 × -
- 11
=
=
∴ The remainder obtained on dividing 3x² + 5x - 11 by 2x + 5 =
#SPJ3
Similar questions